2020
DOI: 10.1177/0886260520915552
|View full text |Cite
|
Sign up to set email alerts
|

Unique, Additive, and Interactive Effects of Types of Intimate Partner Cybervictimization on Depression in Hispanic Emerging Adults

Abstract: The advent of modern technology has inadvertently created newer avenues for intimate partner victimization (IPV) to transpire. This study investigated (a) whether psychological, sexual, and stalking intimate partner cybervictimization (cyber IPV) types were uniquely associated with depression and whether there were (b) additive and (c) interactive effects of cyber IPV types on depression, after controlling for face-to-face IPV among Hispanic emerging adults. Participants were 903 Hispanic emerging adults in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 51 publications
1
20
0
2
Order By: Relevance
“…Prior studies have also found that LGBTQ+ spaces, social networking, and dating applications may represent an essential way to satisfy LGBTQ+ needs such as a sense of existing in a community, receive social approval, and the opportunity to explore different ways to practice their sexuality (Corriero & Tong, 2015; Zervoulis et al, 2020; Miller, 2015). Future studies focusing on IPV in LGBTQ+ emerging adults should include analyses of specific consequences and correlates of cyber IPV, since prior research suggests that cyber IPV could be potentially harmful, generating high levels of distress and consequences in victims, such as an increased consumption of alcohol and greater levels of depression (Cantu & Charak, 2022; Marganski & Melander, 2015; Trujillo et al, 2020). Moreover, stalking behaviors have been related to physical and sexual face-to-face IPV, severe injuries and even homicide; therefore, failure to recognize the potential dangers of cyber stalking and psychological aggressions may have detrimental consequences on LGBTQ+ victim’s mental health (Charak et al, 2019; Messinger et al, 2018; Sargent et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have also found that LGBTQ+ spaces, social networking, and dating applications may represent an essential way to satisfy LGBTQ+ needs such as a sense of existing in a community, receive social approval, and the opportunity to explore different ways to practice their sexuality (Corriero & Tong, 2015; Zervoulis et al, 2020; Miller, 2015). Future studies focusing on IPV in LGBTQ+ emerging adults should include analyses of specific consequences and correlates of cyber IPV, since prior research suggests that cyber IPV could be potentially harmful, generating high levels of distress and consequences in victims, such as an increased consumption of alcohol and greater levels of depression (Cantu & Charak, 2022; Marganski & Melander, 2015; Trujillo et al, 2020). Moreover, stalking behaviors have been related to physical and sexual face-to-face IPV, severe injuries and even homicide; therefore, failure to recognize the potential dangers of cyber stalking and psychological aggressions may have detrimental consequences on LGBTQ+ victim’s mental health (Charak et al, 2019; Messinger et al, 2018; Sargent et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of information and communication technologies (e.g., smartphones and social media), cyberspace has become a popular venue for dating relationships and as a result cyberspace is a platform where IPV can transpire especially in adolescents and emerging adults (Cano-Gonzalez et al, 2022; Cantu & Charak, 2022; Marganski & Melander, 2015; Trujillo et al, 2020; Watkins et al, 2018). Notably emerging adulthood encompasses individuals in the age range from 18 to 29 years old, a developmental stage wherein individuals focus on acquiring new relationships and searching for greater levels of intimacy while simultaneously creating their own identity (Arnett, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A utilização das novas tecnologias acarretou diversos benefícios e, hoje em dia, um aspeto cada vez mais significativo da comunicação nas relações interpessoais dos jovens adultos é o uso das tecnologias de informação e comunicação (TIC) (e.g. internet, telemóveis, mensagens de texto, ou redes sociais) (Cantu & Charak, 2020). Os adolescentes, e também os estudantes universitários, utilizam as novas tecnologias nas suas relações de namoro (Stonard et al, 2017), sendo que as mesmas facilitam a conexão emocional, dado permitirem a interação a qualquer momento (Mosley & Lancaster, 2019;Smith et al, 2018).…”
unclassified
“…Os adolescentes, e também os estudantes universitários, utilizam as novas tecnologias nas suas relações de namoro (Stonard et al, 2017), sendo que as mesmas facilitam a conexão emocional, dado permitirem a interação a qualquer momento (Mosley & Lancaster, 2019;Smith et al, 2018). No entanto, não só de aspetos positivos se constitui esta realidade, uma vez que as novas tecnologias podem também funcionar como um meio para que a violência tenha lugar (Cantu & Charak, 2020), sendo um exemplo o ciberabuso no namoro.…”
unclassified